Kelas Pekerja Dan Pendekatan Lintas Pembilahan (Cross-Cleavage Approach): Studi Kasus Perjuangan Gerakan Sosdem Di Skandinavia - Augusta, Cherry - (Transformasi, 2012)
AbstractThe Scandinavian social democrat’s ability in managing societal cleavages of politics hasbeen an important part in their relative success of promoting the ideas of social democracy, andwelfare state. But there are revived and contested arguments about what kind of cleavages thatmostly played significant role and strategically has been managed to pave the way fordemocratization, and also what kind of approaches used in managing them. Through this paper Icomparatively and definitely emphasize the struggle of working class and social democrats inScandinavia. In which social democrats play highly important role in organizing the workingclass. As apparent in the course of Scandinavia’s democratic history, the working class asdemocratic potential raised significantly when it being organized and enfranchised. Furthermore,the class met typical contexts in capitalism development and traditional cleavages of Scandinavia.The cross-cleavages approaches definitely most used in the struggle, particularly throughoutcoalition with another class, territorial and cultural groups, gender, and even religious groups.Key Word: Social Democrat, Societal Cleavage, Organized Working Class, Croos-CuttingCleavages, Cross-Cleavages Approaches